California mortgage loan brokering and lending - Grogan, D.
Ideal for real estate licensees, individuals seeking to enter the mortgage loan business, and those already actively working in the industry, CALIFORNIA MORTGAGE LOAN BROKERING AND LENDING covers key topics including appraisal, credit agencies, title and escrow, and computer programs used in the industry. Important legal concepts such as trust fund handling and both federal and state compliances are included to meet the state's course requirements. Extensive coverage of necessary forms such as loan application FNMA form, credit authorization, actual escrow instructions are included